2019
DOI: 10.1021/acssensors.9b00994
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond Coating Improves the Sensitivity and Antifouling Properties of Carbon Fiber Microelectrodes

Abstract: Nanodiamonds (NDs) are carbon nanomaterials with a core diamond crystalline structure and crystal defects, such as graphitic carbon and heteroatoms, on their surface. For electrochemistry, NDs are promising to increase active sites and decrease fouling, but NDs have not been studied for neurotransmitter electrochemistry. Here, we optimized ND coatings on microelectrodes and found that ND increases the sensitivity for neurotransmitters with fastscan cyclic voltammetry detection and decreases electrochemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 73 publications
0
55
0
Order By: Relevance
“…ND coatings of different chemical functionalities were applied to carbon fibre microelectrodes (CFMEs) and investigated using the technique fast scan cyclic voltammetry. Decreased fouling as well as improved sensitivity and limit of detection for neurotransmitter sensing was found with ND coatings, Figure 6 (Puthongkham & Venton, 2019). Further to forming films, NDs can be used as part of composites.…”
Section: Fabrication and Application Of Different Diamond Surfaces Fomentioning
confidence: 99%
See 1 more Smart Citation
“…ND coatings of different chemical functionalities were applied to carbon fibre microelectrodes (CFMEs) and investigated using the technique fast scan cyclic voltammetry. Decreased fouling as well as improved sensitivity and limit of detection for neurotransmitter sensing was found with ND coatings, Figure 6 (Puthongkham & Venton, 2019). Further to forming films, NDs can be used as part of composites.…”
Section: Fabrication and Application Of Different Diamond Surfaces Fomentioning
confidence: 99%
“…(c) CFME and (d) carboxylated ND-coated CFME. Reprinted (adapted) with permission fromPuthongkham, P., & Venton, B. J. (2019).…”
mentioning
confidence: 99%
“…The Venton group optimized drop-cast ND coatings on a CFM and found that the carboxylated ND with a particle size of 15 nm gave the most sensitive DA response with FSCV detection. They showed that the ND coating reduced chemical fouling from 5-HT and 5-hydroxyindoleacetic acid and also decreased biofouling in tissue slices by 50% [ 90 ]. In addition, scientists at the Mayo Clinic reported the first use in humans of a polycrystalline boron doped diamond (BDD) microelectrode for recording in the thalamus; see Figure 2 F [ 54 ].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…CFMEs are often fabricated through proprietary mechanisms, using low-throughput assembly methods, and are designed for industrial processes rather than electrochemical purposes [ 101 ]. Recently, boron doped diamond (BDD) deposition and growth processes were developed that enable the wafer patterning and growth of custom-deposited carbon electrodes [ 96 , 102 , 103 , 104 , 105 ]. Through these growth processes, BDD was grown on tungsten wires and carbon fiber surfaces.…”
Section: Introduction To Carbon-based Sensors For Neurochemical Sementioning
confidence: 99%
“…Through these growth processes, BDD was grown on tungsten wires and carbon fiber surfaces. More recently, custom BDD microelectrodes (BDDMEs) encapsulated with polycrystalline diamond were developed [ 96 , 101 , 104 , 106 , 107 ]. BDD is an attractive material because it has a low background current, a wide potential window, and good biocompatibility [ 108 , 109 , 110 ].…”
Section: Introduction To Carbon-based Sensors For Neurochemical Sementioning
confidence: 99%